A global change in RNA polymerase II pausing during the Drosophila midblastula transition. - Chen, K.; Johnston, J.; Shao, W.; Meier, S.; Staber, C.; Zeitlinger, J. (eLife, 2013)
Massive zygotic transcription begins in many organisms during the midblastula transition when the cell cycle of the dividing egg slows down. A few genes are transcribed before this stage but how this differential activation is accomplished is still an open question. We have performed ChIP-seq experiments on tightly staged Drosophila embryos and show that massive recruitment of RNA polymerase II (Pol II) with widespread pausing occurs de novo during the midblastula transition. However, ?100 genes are strongly occupied by Pol II before this timepoint and most of them do not show Pol II pausing, consistent with a requirement for rapid transcription during the fast nuclear cycles. This global change in Pol II pausing correlates with distinct core promoter elements and associates a TATA-enriched promoter with the rapid early transcription. This suggests that promoters are differentially used during the zygotic genome activation, presumably because they have distinct dynamic properties. DOI:http://dx.doi.org/10.7554/eLife.00861.001.